Screening of Barbers for Hepatitis B and C in Faisalabad - Khurram Sohail Raja; Shakeela Naz; Faria Aslam; Noor Arshad; Amer Hayat (Aziz Fatimah Medical and Dental College, 2020)
Objective: To screen the barbers for Hepatitis B and hepatitis C in Faisalabad. Methodology: This cross-sectional study was performed by the forensic medicine department of private medical college of Faisalabad after approval from institutional ethical committee.  The camp for screening barbers was arranged in September 2019 at Sargodha road, Faisalabad. Barbers from different Hair Saloons of the city were invited 2-3 days before arranging the camp. Fifty-five barbers joined the camp for screening. All relevant information was noted on predesigned pro forma. Informed consent was taken and blood samples were drawn from each participant for qualitative detection of hepatitis B Surface Antigen (HBs Ag) and antibodies to HCV (anti-HCV) using one step rapid test devices (Accurate) that are based on a lateral flow chromatographic immunoassay technique. Statistical analysis was done on SPSS 21. Percentages and frequencies for Reactive and Non- Reactive tests HBs Ag and anti-HCV were determined. Results: During this study 55 barbers were screened for hepatitis C and hepatitis B.  The age range of the screened barbers was 18-35 years. We found that 3 (5.4%) of the barbers were seropositive for hepatitis C and 1 (1.8%) barber was co- infected with hepatitis C and hepatitis B, In contrast to this  none of the barbers was found to have hepatitis B only. Conclusion: HCV infection is an occupational hazard for barbers, while HBV infection is not found in barbers despite low infectious dose.